Pengaruh Peradaban Islam terhadap Kebangkitan Intelektual Eropa - Annisa Ainurrohmah; Achmad Maftuh Sujana; Puput Sri Sukmana; Siti Yuniawati; Siti Maysarah (Departemen Pendidikan Kewarganegaraan dan Ilmu Hukum Universitas Negeri Padang, 2025)
This study aims to analyze the influence of Islamic civilization on the intellectual awakening of Europe through a qualitative approach using library research. Based on historical and scholarly literature, the findings reveal that the Islamic world played a central role in shaping Europe’s intellectual transformation, particularly through the transmission of knowledge from major centers such as Baghdad, Andalusia, and the Latin Translation Movement in Toledo. These contributions include the development of scientific methodology, philosophical rationalism, mathematical sciences, clinical medicine, experimental optics, and institutionalized learning that later became the foundation of modern universities. Intellectual values such as rationality, multicultural openness, and experimental tradition significantly influenced European thought during the Scholastic and Pre-Renaissance eras. The study concludes that Europe’s intellectual revival cannot be separated from the substantial contributions of Islamic civilization, which served as a bridge between classical knowledge and modern science. This research provides a comprehensive understanding of inter-civilizational dynamics in the history of scientific development.